Implementasi Media Podcast dalam Pembelajaran Fikih di MAN 2 Palembang - Via Dina Palenzia; Zulhijra; Ibnu Rozali (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
The purpose of this study is to describe the implementation of Podcast media in Fiqh learning and identify its advantages and disadvantages. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation, with purposive sampling for informants. Analysis followed the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. The findings reveal that Podcast implementation in Fiqh learning at MAN 2 Kota Palembang includes three main stages: planning, implementation, and usage. Planning involves systematic processes like material preparation, curriculum adjustment, presentation format selection, and Podcast production/recording in simple language. Implementation includes preliminary activities (greetings, prayers, goal orientation, apperception), core activities (Podcast playback, additional explanations, Q&A), and closing activities (material reinforcement, positive affirmation, reflection tasks). Podcasts effectively deliver khamar material (definitions, evidence, wisdom of prohibitions), eliciting positive student responses such as increased motivation and understanding, though focus varies. Advantages include flexibility, digital relevance, heightened interest, and comprehension support via repetition. Disadvantages encompass technical barriers (audio quality, signals, playback), limited direct interaction, and ethical content challenges. These findings underscore the need for digital technology integration and teacher training in Fiqh education